Intensive MUET @ UMP - Marziah, Ramli; Noor Azlinda, Zainal Abidin (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
27 March - 25 April 2010. The MUET Unit at CMLHS, UMP had intensified its effort by initiating a MUET Intensive Programme, in assisting UMP students who had registered for the mid year and end of the year MUET examinations. The programme covered four language skills tested for MUET namely writing, listening, reading and speaking. The MUET workshops on Speaking and Writing were carried out at CMLHS Mini Theatre starting from end of March to early May 2010.